God-Self-World Continuum in Tribal Religion - Sashinungla (Poligrafi, 2021)
This article draws on the religions of the indigenous tribes in order to show that religion does not have to be a site of domination and exclusion (human or non-humans). It is not a systematic account of the minutiae of tribal religions. It primarily discusses the god-self-world continuum within a tribal paradigm and looks at the ethical implications of various metaphysical commitments that it instructs. Looking at tribal earth-centred spirituality uncovers many ways to consider “nature” and the place of humans, and contributes to overcoming problems of binary dualisms.